Co-Movement Between Credit Growth and Economic Growth In Indoensia Using WaveLet Coherence Analysis - Nuraini, Rahma; Setiawan Fadjar, Nurman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study examines the dynamic relationship between credit growth and economic growth in Indonesia, with a focus on the underexplored comparison between Commercial Banks and Rural Banks (BPR) over the long term. While previous studies often use static models, this research employs Wavelet Coherence Analysis to capture changes in the relationship across time and frequency from 2004 to 2024. The aim is to identify how credit and GDP interact across different periods. The findings reveal that commercial bank credit generally follows economic growth across short, medium, and long-time horizons, supporting the demand-following hypothesis. In contrast, rural bank credit shows a more mixed pattern often lagging behind GDP in the short term, but leading in the long run, suggesting a supply-leading role. There are also signs of bidirectional influence, indicating a feedback loop between credit and economic activity. These results highlight that the credit–growth relationship in Indonesia is both time-dependent and institution-specific. This study contributes by providing real-world evidence of how commercial and rural banks play distinct and complementary roles in supporting the country's economic development